Patterns of gen Zs' leisure time activity and their needs towards urban recreational parks: a review - Ghani, Nurfaezah; Mansor, Mazlina; Zakariya, Khalilah (Institut Sosial Malaysia (ISM), 2018)
A study on the lifestyle of youth is very important to the provision and design of the recreational park. Generation Z (Gen Z) is people who are born from 1995 through 2010. The study was based on a literature review that describes a conceptual framework on the lifestyle patterns of Gen Z in relation to their leisure time activities and their current needs. The review covers 40 studies from 2008 to 2016 from four fields: epidemiological studies, lifestyle pattern, leisure and recreation, landscape and environmental planning. The focus of the review covers parameters which include the leisure time activities of youth and outdoor space preferences. Leisure time activity involves the different types of voluntary activity like physical, leisure and social activities. Spending leisure time in an outdoor environment gives positive effect on health. The result obtained from the reviews reveal the activities and needs of Gen Z according to Gibson’s theory of affordances and Abraham Maslow’s theory of needs. Therefore, the criteria of space in the recreational park could be revealed for encouraging park use among Gen Z to fulfill the acquisition for a healthy lifestyle.